Penerapan Model Role-Playing untuk Meningkatkan Hasil Belajar IPS Pada Materi Peran Para Tokoh dan Pejuang Kemerdekaan Indonesia di Kelas V UPTD SDN Sejati 5 Camplong Kabupaten Sampang Tahun Pelajaran 2019/2020 - Suharno Suharno (Departement of Mathematics Education, 2023)
School is a place to develop students' abilities. This ability can develop in teaching and learning activities carried out by teachers at school. This study aims to determine the increase in learning outcomes through the application of the Role-Playing Model in Social Studies subjects in Class V. The application of role-playing models in Social Studies subjects is proven to improve learning outcomes, but this learning has weaknesses, namely the different levels of student understanding and takes a long time. In cycle I, student learning outcomes increased from learning outcomes in pre-action, which was originally 7 students (25%) to 8 students (28.57%) and experienced another increase in cycle II to 17 students (60.71%).